Germline mutations in CDH1 are infrequent in women with early-onset or familial lobular breast cancers. Issue 1 (4th October 2010) - Schrader, K A; Masciari, S; Boyd, N; Salamanca, C; Senz, J; Saunders, D N; Yorida, E; Maines-Bandiera, S; Kaurah, P; Tung, N; Robson, M E; Ryan, P D; et al.
Abstract : Background: Germline mutations in CDH1 are associated with hereditary diffuse gastric cancer; lobular breast cancer also occurs excessively in families with such condition. Method: To determine if CDH1 is a susceptibility gene for lobular breast cancer in women without a family history of diffuse gastric cancer, germline DNA was analysed for the presence of CDH1 mutations in 318 women with lobular breast cancer who were diagnosed before the age of 45 years or had a family history of breast cancer and were not known, or known not, to be carriers of germline mutations in BRCA1 or BRCA2 . Cases were ascertained through breast cancer registries and high-risk cancer genetic clinics (Breast Cancer Family Registry, the kConFab and a consortium of breast cancer genetics clinics in the United States and Spain). Additionally, Multiplex Ligation-dependent Probe Amplification was performed for 134 cases to detect large deletions. Results: No truncating mutations and no large deletions were detected. Six non-synonymous variants were found in seven families. Four (4/318 or 1.3%) are considered to be potentially pathogenic through in vitro and in silico analysis. Conclusion: Potentially pathogenic germline CDH1 mutations in women with early-onset or familial lobular breast cancer are at most infrequent.